Influencers of life insurance investments – an empirical evidence from Europe - Mitra, Aditi * (Academy of Business and Retail Management (ABRM), 2016)
The main purpose of the study is to identify the economic, cultural and demographic determinants of life insurance consumption for 28 European countries. The study used panel data analysis techniques over the post financial crisis period 2009-2014 and considers many of the emerging Eastern European economies where there have been significant insurance sectors reforms recently. Europe is the largest insurance market with 35% of the overall insurance premium contribution but ranked third in insurance per capita in 2014, hence Europe is an interesting region to study the insurance demand. Among the explanatory variables assumed in the study, gross savings, inflation, GDP and openness of economy (economic variables), population (demographic variable), power distance, uncertainty avoidance, long term orientation and individualism (cultural variables) have been observed to have a significant impact on life insurance demand in the European region.